Strengthening Democratic Values Through Public Information Services: The Role Of Regional PPID Officials In Cilegon City - Ibrohim Ibrohim; Muhammad Ali; Casnika Casnika; Gautam Kumar Jha (Yayasan Cendekia Gagayunan Indonesia, 2025)
The purpose of this study is to explain the role of the Information and Documentation Management Officer (PPID) of the Regional Public Agency in Cilegon City, Banten Province, the Cilegon City public agency which consists of the PPID of the Regional Apparatus Organization (OPD) which carries out executive functions in the region. In its history, the Cilegon City Government in 2019 had the lowest score in delivering information, namely with a score of 60.34 with a fairly informative qualification from all cities and districts in Banten Province, but in 2023 it was ranked 3rd after Serang Regency, this indicates the need for efforts to strengthen the role of PPID especially in Cilegon City. The method used in this study uses normative legal research, namely by using a data analysis approach with a study of statutory regulations (statute approach), the data analysis used is by using descriptive analysis, namely analyzing statutory regulations and comparing them with legal events based on their implementation. The results of the study explain that the role of PPID is very important to support information and documentation in the regions, especially the city of Cilegon, and the consequences for PPID public bodies that do not convey information transparently can have legal consequences, the legal settlement process can be carried out in two ways, namely through litigation and non-litigation.